Traditional Indian Medicinal Plants for the Treatment of Psoriasis: A Review of Active Constituents and their Pharmacological Effects - Sarkar, Dhrubajyoti; Das, Soma; Kalita, Pallab; Jyoti Pathak, Bhaskar; Judder, Moidul Islam; Datta, Kunal; Alam, Faruk (Journal of Natural Remedies, 2023)
Psoriasis is a chronic inflammatory skin disease that affects millions of people worldwide. The use of natural products for the treatment of psoriasis has gained interest due to their potential to modulate the immune system and reduce inflammation. Traditional Indian medicinal plants offer a promising source of natural products for the treatment of psoriasis. This article provides a comprehensive review of Indian medicinal plants that have been traditionally used for the treatment of psoriasis, along with their active constituents and reported pharmacological activities. In addition, we discuss the molecular pharmacology of psoriasis and the limitations of current allopathic treatment methods. Finally, we highlight the potential therapeutic effects of individual active constituents found in Indian medicinal plants, with a focus on their anti-inflammatory, antioxidant, and immunomodulatory properties. This review provides a basis for further research on the use of traditional Indian medicinal plants for the treatment of psoriasis.